Andrzej Kijowski wobec Karola Wojtyły - Jana Pawła II: tekstowy obraz doświadczenia osoby = Andrzej Kijowski on Karol Wojtyla-John Paul II: a textual picture of the person`s experience - Tomaszewska, Wiesława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article reconstructs the textual image of the person of Karol Wojtyla-John Paul II. An analysis of Andrzej Kijowski`s texts is made through a category that is important for the philosophical thought of Wojtyla, i.e. the experience of the person, one`s own "self" and another man.
Keywords: Jan Paweł II, papież (1929-2005); Kijowski, Andrzej (1928-1985); literatura polska - 20 w.